The name-bearing type of Oligodon quadrilineatus (Jan & Sordelli, 1865) (Squamata: Colubridae) - David, Patrick; Vogel, Gernot; van Rooijen, Johan; Pierre, Laure (Zootaxa, 2011)
David et al. (2008) revised the nomenclature and systematics of the Asian colubrid snakes recognized in the literature as the “Oligodon taeniatus-group”. In order to fix the status of Simotes quadrilineatus Jan & Sordelli, 1865, David et al. (2008) designated a neotype. Although Jan & Sordelli (1865: Plate IV: Fig. 3) depicted only one specimen, David et al. (2008) pointed out that four specimens were considered syntypes of S. quadrilineatus in the catalogues of the Muséum national d’Histoire naturelle, Paris (MNHN), all collected by F. Bocourt in Siam between December 1861 and July 1862 (Milne-Edwards 1866; Bocourt 1866). Thanks to the precision of Jan & Sordelli’s drawing of the ventral pattern, in which ventral blotches are clearly visible, it appeared that none of these four specimens was the holotype depicted on Plate 4 of Jan & Sordelli (1865). As a consequence, David et al. (2008) designated as neotype MNHN 1991.1819, an adult female from “Bangkok”, Thailand, belonging to the series collected by F. Bocourt.